Choice of health metrics for combined health and environmental assessment of foods and diets: A systematic review of methods. (10th September 2022) - Guo, Annie; Bryngelsson, Susanne; Strid, Anna; Bianchi, Marta; Winkvist, Anna; Hallström, Elinor
Abstract: Evidence-based scientific methods combining health and environmental perspectives are urgently required to support policy decisions and recommendations for more sustainable food systems. This review provides a systematic overview of health metrics and methods to combine health and environmental assessment of foods and diets. Key methodological considerations of importance for best practices are highlighted as well as trends over the past decade, and future research needs. A systematic literature review was performed in the databases Scopus, Dimensions and Pub Med. Eligible articles combined health impact and environmental assessment of food and were published in peer-reviewed scientific journals between 2010 and 2020. Differences in method choices were highlighted based on study approach, dietary baseline data, dietary exposure, dietary-related health outcome, method for health assessment, choice of health metric, environmental outcome and method for combined health and environmental assessment. A total of 33 articles using nine different health metrics in combination with environmental assessment of foods were identified. Avoided, averted, delayed or preventable deaths or cases, followed by disability- or quality-adjusted life years, and hazard ratio were the health metrics most commonly used. Three principal methods to combine health and environmental assessment of foods and diets were identified; parallel assessment (n = 26), scaled assessment (n = 7) and integrated assessment (n = 1). Method choices affecting reliability and uncertainty, as well as suitability for different purposes were described. Over the past decade, a strong acceleration in the research field of combined health and environmental assessment of food was noted, both regarding number of published studies and method development for more holistic sustainability assessments. Transition towards more sustainable food choices offers great potential to improve public health and reduce environmental impact from the food system. This review identified several health metrics that are suitable for use in methods combining health and environmental dimensions when studying the sustainability of food systems. For best practices, improved knowledge on how multi-criteria sustainability indicators can be assessed, communicated and implemented by different actors along the food supply chain is required. Graphical abstract: Image 1 Highlights: Strong increase in health and environmental assessments of food between 2010 and 2020. Outline of key method aspects for multi-criteria food sustainability assessments. Nine health metrics combined with environmental assessment of food were identified. Health and environment were combined by parallel, scaled or integrated assessment. A trend of more holistic food sustainability assessments was identified.